Assembly of fission yeast eisosomes in the plasma membrane of budding yeast: import of foreign membrane microdomains - Vaskovicova, Katarina; Stradalova, Vendula; Efenberk, Ales; Opekarova, Miroslava; Malinsky, Jan (European journal of cell biology, 2015)
Eisosomes are plasma membrane-associated protein complexes organizing the membrane compartment of Can1 (MCC), a membrane microdomain of specific structure and function in ascomycetous fungi. By heterologous expression of specific components of Schizosaccharomyces pombe eisosomes in Saccharomyces cerevisiae we reconstitute structures exhibiting the composition and morphology of S. pombe eisosome in the host plasma membrane. We show S. pombe protein Pil1 (SpPil1) to substitute the function of its S. cerevisiae homologue in building plasma membrane-associated assemblies recognized by inherent MCC/eisosome constituents Sur7 and Seg1. Our data indicate that binding of SpPil1 to the plasma membrane of S. cerevisiae also induces formation of furrow-like invaginations characteristic for MCC. To the best of our knowledge, this is the first report of interspecies transfer of a functional plasma membrane microdomain. In the described system, we identify a striking difference between eisosome stabilizer proteins Seg1 and SpSle1. While Seg1 recruits both Pil1 and SpPil1 to the plasma membrane, SpSle1 recognizes only its natural counterpart, SpPil1. In the presence of Pil1, SpSle1 is segregated outside the Pil1-organized eisosomes and forms independent microdomains in the host membrane.
Keywords: Membrane microdomain; Saccharomyces cerevisiae; membránové proteiny; Membrane Proteins; Phosphoproteins; Cell Membrane; fosfoproteiny; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; Schizosaccharomyces pombe Proteins; Schizosaccharomyces pombe - proteiny; Plasma membrane; Cytoskeletal Proteins; membránové mikrodomény; cytoskeletální proteiny; Schizosaccharomyces; Eisosome; Membrane Microdomains; buněčná membrána; MCC